Hak Kekayaan Intelektual Sebagai Wakaf Produktif yang Potensial (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Waqf as an instrument for increasing the welfare ummah is seriously have done by the expansion of waqf property objects. The idea of waqf with movable objects emerged in 2004 with the birth of Law No. 41 of 2004 concerning Waqf. One of the interesting things in Article 16 of the law is the inclusion of provisions which state that Intellectual Property Rights can be used as waqf assets. in this article the author discusses intellectual property such asÂ Â patents and copyrights that have the potential as endowments. the purpose of writing this article is also as a form of information for the public to better understand intellectual property rights as endowments and the potencial of propert rights as productive waqf.